2017
DOI: 10.1177/0268355517717404
|View full text |Cite
|
Sign up to set email alerts
|

A sonographic study of thigh telangiectasias

Abstract: Introduction To date, there are limited descriptive data on the ultrasonographic characteristics of reticular and perforator veins associated with telangiectasias of the thigh. Objectives Evaluate the prevalence, anatomic correlations of reticular and perforator veins associated with lateral thigh telangiectasias. Methods This was a cohort study performed between June and December of 2014. Twenty-four female patients (43 limbs) with telangiectasias of the lateral thigh were evaluated by duplex ultrasound. Reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…208 The general idea is that chronic venous disease refluxes must be treated before the aesthetic component, so to avoid venous hypertension potentially triggering recurrences. To the best of our knowledge, limited evidence-based data 209 , 210 are available on this topic and future investigations should clarify this common belief, even if rightfully based on the concept that the treatment of a pathological aspect should always precede the aesthetic issue. Moreover, future research lines should try to make the different telangiectasia classifications more homogeneous, incorporating both morphological (spider, arboriform, filiform, point-like, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…208 The general idea is that chronic venous disease refluxes must be treated before the aesthetic component, so to avoid venous hypertension potentially triggering recurrences. To the best of our knowledge, limited evidence-based data 209 , 210 are available on this topic and future investigations should clarify this common belief, even if rightfully based on the concept that the treatment of a pathological aspect should always precede the aesthetic issue. Moreover, future research lines should try to make the different telangiectasia classifications more homogeneous, incorporating both morphological (spider, arboriform, filiform, point-like, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Raymond-Martinbeau et al 24 found a direct relation between reticular veins and telangiectasias in 71% of the cases; and Mariani et al 25 even found connections in 100% of the 200 areas of telangiectasias examined with side-illumination and Doppler. In a duplex ultrasonographic study of 43 asymptomatic limbs with lateral thigh telangiectasias, 26 all limbs had incompetent reticular veins. Twenty incompetent perforators were connected to the reticular veins.…”
Section: Pathophysiological Hypothesismentioning
confidence: 97%
“…In a sonographic study of thigh telangiectasias, 26 obese and overweight patients (BMI > 25) presented a significant higher prevalence of incompetent perforators and reticular veins, and had a larger diameter when compared to normal weight.…”
Section: Risk Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Obese and overweight patients had a higher frequency of incompetent perforator veins and larger reticular veins compared to when compared to those with normal weight (P < 0.05). 53 The same process was applied to C1 patients to determine whether ultrasound mapping of the saphenous veins is justified. There was a statistically significant tendency that the increased presence of incompetent deep and/ or superficial venous incompetence also increases the presence of telangiectasias.…”
Section: Diagnostic Testsmentioning
confidence: 99%